Dealing with the COVID-19 pandemic: an opportunity to reflect on sustainability research - Benjamin Nölting; Bettina König; Anne B. Zimmermann; Antonietta Di Giulio; Martina Schäfer; Flurina Schneider (Sustainability Management Forum, 2022)
The COVID-19 pandemic has jolted societies out of normality, possibly creating new conditions for sustainability transformations. What does this mean for sustainability research? Because of the scope of the crisis, researchers have been heavily involved: not only have they had to speed up the pace of scientific production to provide urgently needed COVID-19 knowledge, but they have also been affected citizens. For sustainability science, this calls for an experience-based reflection on the positionality and orientation of research aiming to support sustainability transformations. Twenty sustainability researchers discussed their sustainability research on COVID-19 in three workshops based on the following questions: How does the pandemic—and the measures taken to deal with it—affect sustainable development? What can we learn from the pandemic from the perspective of societal transformation? The present discussion paper emerged from this multidisciplinary exchange among sustainability researchers, considering five topics: impacts of the COVID-19 crisis on sustainability transformations; learning for sustainability transformations; the role of solidarity; governance and political steering; and the role of science in society. Our discussions led to a~meta-level reflection on what sustainability research can learn from research on COVID-19 regarding topics and disciplinary angles, time dimensions, the role of researchers, and how adequate preparation for both crises and long-term transformations requires interdisciplinary interaction.
Keywords: 650; COVID-19; Corona pandemic; Sustainable development; Sustainability research; Interdisciplinarity; Transformation; Reflection